Human leukemia cells photoinactivation employing an anthraquinone from Argentinean flora - Mugas, María Laura (2019)
Parietin (PTN), an anthraquinone (AQ) found in some vegetal species even lichens, has been shown to be a good photosensitizer with promising applications in bacterial photoinactivation. The aim of this work was to evaluate the in vitro activity of PTN as photosensitizer on K562 human leukemic cells; in order to estimate its potential use in Photodynamic Cancer Therapy (PDT).PTN (1,8-dihydroxy-3-methoxy-6-methylanthraquinone) was isolated from the lichen Teoloschistes nodulifer (Nyl.) Hillman (Teloschistaceae) and it was purified by recrystallization from the acetone extract, and its purity was determined by HPLC.